Pengaruh Pencemaran Limbah Detergen Terhadap Ekosistem Perairan - Lestari, Andriani Dwi (Jurnal Sains Indonesia, 2022)
Detergent is a product that has the use to remove dirt when purifying clothes. If detergents are excessively discharged into water sources, it can have a negative impact on water biota, such as reducing oxygen levels in water and damaging fish organs because it can cause water pollution. Where the higher the use of detergents, the lower the intake of dissolved oxygen in the water. This causes disruption of the process of respiration in the ecosystems such as fish that can cause death in fish. This type of research is qualitative research using experimental methods conducted by observing the movement of fish in water conditions without detergents up to detergent for 10 minutes. The object of this study is ornamental fish that are treated without the addition of detergents and then added one spoon of detergent, two spoons of detergent, up to three spoons of detergent. The parameters studied were the condition of the fish when added with detergent with different treatments. The results showed that the difference in the concentration of determination on the condition and life of the fish. The higher the concentration of detergent, the fish will live. Then seen in conditions, then the fish will be disturbed breathing, namely on the gills. Gills are vital organs of fish respiration. organ damage and fish skin that becomes slimy is also due to the detergent content. Until the fish die because of contaminated toxic materials.